The Influence of Green Training, Green Recruitment and Green Transformational Leadership on Sustainable Corporate Performance at PT Kima Makassar - Ruma, Zainal (PT. Maju Malaqbi Makkarana, 2024)
The aim of this research is to evaluate the influence of Green Training, Green Recruitment, and Green Transformational Leadership on Sustainable Corporate Performance separately and simultaneously. In this research, a quantitative approach was used, and the sample was 100 people who worked at PT KIMA Makassar. The research results show that Green Training (X1) partially has a positive and significant impact on Sustainable Corporate Performance. The calculated t value is 3.165, lower than the t table value of 1.984, and the significance value is 0.003, less than 0.05. Apart from that, Green Training also has a positive and significant impact on Sustainable Corporate Performance, with a calculated t value of 4.181, which exceeds the t table of 1.984, and a significance value of 0.000 below 0.05. On the other hand, Green Transformational Leadership also has a positive impact on Sustainable Corporate Performance, with a calculated t value of 7.019, which exceeds the t table of 1.984, and a significance value of 0.000 below 0.05. Apart from that, a simultaneous test was carried out on the influence of Green Training (X1), Green Recruitment (X2), and Green Transformational Leadership (X3) on Sustainable Corporate Performance. The results show a calculated f of 78.706, which exceeds the f table of 2.70, and a significance value of 0.000 is less than 0.05.